1992
DOI: 10.3109/02713689209015076
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal and Subretinal Proliferation Induced by Platelet-Rich Plasma Injection in Rabbits

Abstract: We developed an experimental model of proliferative vitreoretinopathy (PVR) in albino rabbits by combining some factors suspected of causing the disease. Sixty nine eyes divided into six groups served as controls (Groups C 1-6). Forty nine eyes were divided into four experimental groups (Groups E 1-4). Group E1 (n = 12) was injected with 0.15 ml of platelet-rich plasma. In addition, Groups E2 (n = 12) and E3 (n = 12) underwent cryotherapy or vitrectomy. Group E4 (n = 13) underwent both procedures. Seven of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…In 1992, the hypertrophy of Müller cells was detected by our group in a rabbit model of PVR (Pinon et al, 1992). However, we were not able to recognize the importance of this finding, probably because we were under the influence of the pathogenesis ideas of the original description of PVR.…”
Section: Role Of Glial Cellsmentioning
confidence: 66%
See 1 more Smart Citation
“…In 1992, the hypertrophy of Müller cells was detected by our group in a rabbit model of PVR (Pinon et al, 1992). However, we were not able to recognize the importance of this finding, probably because we were under the influence of the pathogenesis ideas of the original description of PVR.…”
Section: Role Of Glial Cellsmentioning
confidence: 66%
“…Both strategies of retinopexy induce a pro-inflammatory environment that could explain the high risk as shown in experimental models Goldaracena et al, 1997;Pinon et al, 1992). Indeed, in a prospective, randomized, placebo-controlled, double-blind clinical trial performed to determine if prolonged administration of systemic corticosteroids would attenuate early stages of PVR, the application of transcleral cryocoagulation was associated with more cases developing epiretinal membranes in the placebo than the steroid group (Koerner et al, 2012).…”
Section: Preoperative Intraoperative and Postoperative Risk Factorsmentioning
confidence: 95%
“…However, these models are flawed because they introduce large numbers of cells. Moreover, they do not take into account the early crucial steps in PVR development, including cellular transformation and proliferation [53, 89, 90]. If the inhibitory effects of any drugs are tested, injected drugs may affect not only the development of PVR but also the injected cells themselves directly.…”
Section: Limitation Of Current Animal Models Research Needs and Futmentioning
confidence: 99%
“…However, previous models using auto-or homologous platelets [14] only lead to moderate vitreous strands, without retinal detachment, unless associated with large traumatism [15], vitrectomy, lensectomy or cryotherapy [16]. Kono et al [17] showed the development of epiretinal membranes in albino rabbits following injections of autologous white blood into the vitreous cavity.…”
Section: Discussionmentioning
confidence: 99%